DESTINASI WISATA PELABUHAN PENDINGIN: INTEGRASI SOSIAL SEBAGAI JEMBATAN PERUBAHAN - Nur Anis Rochmawati (LPPM STAIMAS WONOGIRI, 2021)
Judging from geographical conditions and demographic potential, Pendingin can be said to have quite a lot of assets. With progressive development, it will lead it to become an independent village. The ABCD (Asset Based Community-driven Development) method can help bridge the mentoring process that aims to change the mindset and awareness of regional potential. The cultivation of attitudes can be started with a mental revolution movement through the activities of making tourist destinations. This can be the initial milestone for a mindset change, that Pendingin has unlimited potential and for the development process depending on how creative and innovative the residents are.